After-hours elective spine deformity corrective surgery for patients with Adolescent Idiopathic Scoliosis: Is it safe?. (4th April 2019) - Chiu, Chee Kidd; Chan, Chris Yin Wei; Chandren, Josephine Rebecca; Ong, Jun Yin; Loo, Shweh Fern; Hasan, Mohd Shahnaz; Kwan, Mun Keong
Objective: The aim of this study was to compare the outcome of after-hours electively planned Posterior Spinal Fusion surgeries for Adolescent Idiopathic Scoliosis (AIS) patients with daytime surgeries. Methods: This was a retrospective propensity score-matched study using prospectively collected data. Surgeries performed between 08:00 and 16:59 h were labeled as daytime surgeries (group 1) and surgeries performed between 17:00 and 06:00 h were labeled as after-hours surgeries (group 2). The perioperative outcome parameters were average operation time in and out, operation duration, intraoperative blood loss, blood transfusion, intraoperative hemodynamic parameters, preoperative hemoglobin, postoperative hemoglobin, and total patient-controlled anesthesia (PCA) morphine usage. Radiological variables assessed were Lenke subtypes, preoperative Cobb angle, number of fusion levels, number of screws used, postoperative Cobb angle, correction rate, side bending flexibility, side bending correction index, complications rate, and length of hospitalization. Results: Average operation time in for daytime group was 11:32 ± 2:33 h versus 18:20 ± 1:05 h in after-hours group. Comparing daytime surgeries with after-hours surgeries, there were no significant differences ( p > 0.05) in the operation duration, intraoperative blood loss, intraoperative pH, bicarbonate, lactate, postoperative hemoglobin, hemoglobin drift, blood transfusion, postoperative Cobb angle, correction rate, side bending flexibility, side bending correction index, length of hospitalization, and complications rate. Total PCA morphine usage was significantly lesser in the after-hours group (18.2 ± 15.3 mg) compared with the daytime group (24.6 ± 16.6 mg; p = 0.042). Conclusions: After-hours elective spine deformity corrective surgeries for healthy ambulatory patients with AIS were as safe as when they were done during daytime.